A Framework for Malaysian Construction Industry Young Professionals (CIYPs) Contractual Employment Contract: A Conceptual Paper - Hawa Mohd Kasmuri, Siti; Ismail, Zulhabri; Mohd Nordin, Rumaizah; Hashim, Norfashiha; Emanuel Ndekugri, Issaka; Rashdan Abd Rahman, Mohd (International Journal of Engineering and Technology, 2018)
As the construction industry is important to the Malaysian economy, employment issue should be managed accordingly. However, there is lack of employment protection under the Malaysian employment legislation for employees with earnings of RM 2,000â€“RM 5,000 (USD 486â€“USD 1,213) per month and are also categorised as the young professionals. Even with additional jurisdiction given to the Director General of Labour, the minimum protection is not mandatory to be imposed, hence resulting in unfair employment practices. This paper aims to propose the conceptual framework for future study. This study adopts the approach in reviewing literatures to confirm the findings from preliminary interviews conducted with the labour officers from the Department of Labour (DoL) of Peninsular Malaysia. It is confirmed that the fairness element in employment can be achieved through roles played by the organisations and supports given from policymakers. The finding encourages good employment practices with fairness element as the focal point that benefits the industry and policymakers. Â